(untitled) (Advancements in Homeopathic Research, 2025)
Psoriasis is one of the most common skin diseases. Psoriasis is thought to be an immune system problem that causes the skin to regenerate faster. The cause is believed to be genetics and environmental factors play a role. Homeopathy, however provides a better response in such condition, one such case report is presented below. Patient attended outdoor patient department (OPD) chiefly for complaints of erythematous plaques with silvery scales on the elbows, knees, and scalp, accompanied by pruritus and occasional bleeding due to scratching. He was suffering from psoriasis since 5 years. After unsatisfactory outcome from modern medicine, patient turned to homoeopathic treatment in our OPD. After case taking and repertorization, Nux vomica was prescribed and gradually the potency was increased as per response of medicine upon patient.